Work, Ergonomics and Industrial Relations - Lamonde, Fernande; Montreuil, Sylvie (Relations industrielles / Industrial Relations, 1995)
Two objectives are pursued: to define the object of study, the objectives and the methodology that are characteristic of ergonomics, and to highlight the common points and possibilities of collaboration between industrial relations and ergonomics. The interest inherent in a collaboration between these 2 disciplines is explained, among other things by a historical coincidence. On the ergonomics side, a period that concentrated on developing concrete ways of collaborating with technical disciplines like engineering, computing and architecture has given way to a focus on work organization and the social management aspect of ergonomics intervention. At the same time, industrial relations has developed a more pronounced interest in the practical management problems that are posed by micro-organizational processes within firms, namely, the informal work activities of operators.
Keywords: Business And Economics--Labor And Industrial Relations; Business And Economics--Personnel Management; Ergonomics; Labor Unions; Labor relations; Objectives; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z